Dose-dependent reductions in plasma ceramides after anthocyanin supplementation are associated with improvements in plasma lipids and cholesterol efflux capacity in dyslipidemia: A randomized controlled trial. Issue 4 (April 2021) - Zhao, Yimin; Xu, Huihui; Tian, Zezhong; Wang, Xu; Xu, Lin; Li, Kongyao; Gao, Xiaoli; Fan, Die; Ma, Xilin; Ling, Wenhua; Yang, Yan
Summary: Background & aims: Plasma ceramides have been identified as novel risk factors for metabolic and cardiovascular diseases. We aimed to evaluate the effects of dietary anthocyanins on plasma ceramides and to disentangle whether the alterations in ceramides could be related with those in other cardiometabolic risk factors in the dyslipidemia. Methods: In a randomized double-blinded placebo-controlled trial, 176 eligible dyslipidemia subjects were randomly assigned into four groups receiving placebo, 40, 80, or 320 mg/day anthocyanins, respectively for 12 weeks. Results: A total of 169 subjects completed the study. After 12-week intervention, dietary anthocyanins dose-dependently reduced plasma concentrations of all six ceramide species in the dyslipidemia subjects (all P trend values < 0.05). Specifically, 320 mg/day anthocyanins effectively lowered plasma N -palmitoylsphingosine (Cer 16:0, mean change: −28.3 ± 41.2 versus 2.9 ± 38.2, nmol/L, P = 0.018) and N -tetracosanoylsphingosine (Cer 24:0, mean change: −157.1 ± 493.9 versus 10.7 ± 439.9, nmol/L, P = 0.002) compared with the placebo. The declines in plasma Cer 16:0 and Cer 24:0 were significantly correlated with the decreases in plasma non-high-density lipoprotein cholesterol (nonHDL-C, Spearman's r = 0.32, P = 0.040 for Cer 16:0; Spearman's r = 0.35, P = 0.026 for Cer 24:0), apolipoprotein B (Spearman's r = 0.33, P = 0.031 for Cer 16:0; Spearman's r = 0.48, P = 0.002 for Cer 24:0), and total cholesterol (Spearman's r = 0.34, P = 0.026 for Cer 16:0; Spearman's r = 0.31, P = 0.042 for Cer 24:0) after 12-week 320 mg/day anthocyanin administration. Besides, we found that anthocyanins at 320 mg/day also markedly enhanced cholesterol efflux capacity in the dyslipidemia, the changes of which were positively associated with the reductions in Cer 16:0 (Spearman's r = 0.42, P = 0.006) independent of HDL-C and apolipoprotein A-I. Conclusions: Reductions in plasma Cer 16:0 and Cer 18:0 after 12-week anthocyanin intervention were dose-dependently associated with improvements in plasma lipids and cholesterol efflux capacity in the dyslipidemia. Clinical trial registration: The study was registered at ClinicalTrials.gov with the identifier No. NCT03415503.